Diversidade da entomofauna associada à Olea europaea (Linnaeus, 1953) em Formigueiro, Rio Grande do Sul - Silva, Jéssica Maus da (2018)
This study was developed with aim evaluate insect fauna, verify the possible pest insects and their damages caused in olive culture. Data were collected in olive orchard located in the municipality of Formigueiro, state of Rio Grande do Sul, Brazil. In three articles, which consist in a bibliographical review of the main diseases and pest insects present in the olive culture, evaluation of the population fluctuation of bark beetles in olive orchard, characterization the diversity of insects associated with olive crown and their main pest insects. Results of this study allow to help the management of the culture and encourage the producers to expand the olive culture in the country.